1993
DOI: 10.1103/physrevb.47.8471
|View full text |Cite
|
Sign up to set email alerts
|

White lines andd-electron occupancies for the 3dand 4dtransition metals

Abstract: We used electron-energy-loss spectrometry to measure the intensities of the white lines found at the onsets of the L2 and L3 absorption edges for most of the 3d and 4d transition metals. The intensities of the white lines, normalized to the trailing background, decreased nearly linearly with increasing atomic number, rejecting the filling of the d states. One-electron Hartree-Slater calculations of the white-line intensities were in good agreement with observed spectra. Empirical correlations between normalize… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
355
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 406 publications
(393 citation statements)
references
References 35 publications
17
355
1
Order By: Relevance
“…This result proves that the normalization technique introduced by Pearson et al 6 is less sensitive to the variation of the valence state. Therefore, the L 3 /L 2 ratio image is likely to be the most sensitive technique for mapping the valence distribution.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…This result proves that the normalization technique introduced by Pearson et al 6 is less sensitive to the variation of the valence state. Therefore, the L 3 /L 2 ratio image is likely to be the most sensitive technique for mapping the valence distribution.…”
Section: Resultssupporting
confidence: 62%
“…EELS experiments have shown that a change in the valence states of cations introduces significant variation in the intensity ratio of the white lines, giving the possibility of identifying the occupation number of 3d or 4d electrons (or cation valence states) using the measured white line intensities. 6,7 The information obtained using EELS is an integration over the spatial region illuminated by the incident electron beam. In this paper, we introduce a new experimental approach which can give the distribution maps of cation valences in real space, allowing a direct identification of cations with different valence states.…”
mentioning
confidence: 99%
“…To reduce scatter, a subtracted using either of two methods. The first method is second method using a zero-slope, two-step function was similar to the two-step function used by Pearson et al [86], applied. The second background fitting procedure is and is illustrated in Fig.…”
Section: Eels L 3 /L 2 Ratio Of Integrated Intensitymentioning
confidence: 99%
“…Pearson et al (1993) and Mattheiss & Dietz (1980) report a procedure by which EELS can provide information about the local occupation of 3d states in transition metals. They show that the sum of the intensities of the white lines (with the excitations to continuum removed) can be related to the occupancies of the corresponding outer d states.…”
Section: Introductionmentioning
confidence: 99%